Sincere Charity from the Perspective of Islamic Religious Teachings - Muhammad Nursyauqi; Uus Husni Hoer; Natasya Ramadina Azura; Rizki Abdul Basir (Penerbit Hellow Pustaka, 2025)
Sincerity is carrying out good deeds solely because of Allah SWT, who is the cause of one's sincerity as a spirit for all valuable deeds with Allah. However, sincerity today has begun to fade, because many people have started with their ego. It is as if we want to feel that our deeds are better than the people who are followed. So that at the end a complete explanation can be produced and can increase our understanding of the interpreter's view of sincerity in charity. The problems examined in this thesis are: The results of this study can be concluded that sincere is to clean the liver from all contamination, not a little or a lot. Thus, the intention to taqarrub to Allah becomes pure and there is no motive to do anything other than because of Him. The manifestation of sincerity is a matter that is easy to do, and it is in the hands of whoever wants it. To achieve it can be done with light effort without bothering and without being serious. Even though in reality, realizing sincerity is not an easy matter because the human heart is always turning back and forth.